Time-period Measurements of Reversible Pendulum Using Arduino - Wadhwa, Adya; Singh, Manmohan; Kumar, Kuldeep; Wadhwa, Ajay (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: The purpose of this study is to improve the Kater’s reversible pendulum experiment by integrating an Arduino microcontroller and infrared sensor to obtain more accurate, reliable, and automated measurements of oscillation periods for determining the acceleration due to gravity. Methodology: The methodology used in this study includes Kater’s reversible pendulum, Arduino Uno microcontroller (Arduino, Italy), infrared (IR) sensor, digital stopwatch (Casio HS-3V-1R), personal computer with Arduino IDE software, data recording using Microsoft Excel, and review of related literature and student feedback survey. Main Findings: The main findings of this study show that the modified Kater’s reversible pendulum integrated with Arduino Uno and an infrared sensor successfully automated oscillation measurements, minimized human error, and improved timing accuracy. The system produced a reliable value of gravitational acceleration, g = 9.85 m/s², confirming high precision and effectiveness of the experimental setup. Novelty/Originality of this study: The novelty of this study lies in modifying the traditional Kater’s reversible pendulum by integrating an Arduino Uno and infrared sensor for automated oscillation measurement. This innovation advances existing methods by reducing human error, improving precision, and providing students with exposure to modern microcontroller applications, thereby enhancing both experimental accuracy and educational value.